Assessing the impacts of COVID-19 on the coffee value chain in Guatemala: Evidence from coffee growers in the Midwest and East - Hernandez, Manuel A.; Ceballos, Francisco; Paz, Cynthia; Berrospi, Maria Lucia (International Food Policy Research Institute, 2021)
Coffee is a growth market. Current estimates indicate that global coffee production (in volume) has increased by more than 60% since the 1990s. Coffee is produced by around 25 million farmers, which are mainly smallholders in developing and least developed countries, and over 70% of the coffee produced is exported, resulting in about 20 billion US dollars annual foreign exchange earnings (ICO, 2020). COVID-19 represented a severe joint supply and demand shock to the global coffee sector, particularly during the first months after the start of the pandemic. As noted by Hernandez et al. (2020), the coffee industry experienced important disruptions downstream the value chain, including the functioning of key export infrastructure and international shipping, which combined with local currency devaluations and volatile coffee prices, which resulted in significant challenges for coffee growers, farm workers, and traders.